2017
DOI: 10.1111/evj.12713
|View full text |Cite
|
Sign up to set email alerts
|

Do different characteristics of two emasculators make a difference in equine castration?

Abstract: These results suggest it may be preferable to use a Reimer emasculator in open castration. In this ex vivo model of closed castration, no differences between the emasculators were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Different types of emasculators have different jaw profiles and different mechanisms of haemostasis and resection (Comino et al, 2018). A recent study by Comino et al (2018) found that in contrast to previous studies (Kilcoyne et al, 2013), the Reimer castrator had a higher‐pressure resistance than the Serra castrator in open castrations.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of emasculators have different jaw profiles and different mechanisms of haemostasis and resection (Comino et al, 2018). A recent study by Comino et al (2018) found that in contrast to previous studies (Kilcoyne et al, 2013), the Reimer castrator had a higher‐pressure resistance than the Serra castrator in open castrations.…”
Section: Complicationsmentioning
confidence: 99%
“…Different types of emasculators have different jaw profiles and different mechanisms of haemostasis and resection (Comino et al, 2018). A recent study by Comino et al (2018) found that in contrast to previous studies (Kilcoyne et al, 2013), the Reimer castrator had a higher‐pressure resistance than the Serra castrator in open castrations. The Henderson Equine Castrating Instrument is a pliers‐like instrument attached to a power drill, that twists the spermatic cord, rather than cutting, resulting in sealing the severed vessels.…”
Section: Complicationsmentioning
confidence: 99%